Strategi Bertahan Hidup Petani dalam Menghadapi Ketidakpastian Harga Komoditas Pertanian di Desa Margaluyu Kabupaten Bandung - Ambarwati, Deya; Aprilia, Hilda; Lintang, Najwa; Anggraeni, Nurdian; Fauzan Rahmadani, Muhamad; Ifan, Muhammad (Jurnal Multidisiplin Indonesia, 2024)
This study aims to analyze the survival strategies used by farmers in Margaluyu Village, Bandung Regency, in dealing with the uncertainty of agricultural commodity prices. The instability of agricultural product prices is one of the main challenges faced by farmers, which has an impact on their economic and social welfare. A qualitative descriptive approach was used in this study with data collection techniques through in-depth interviews, observation, and documentation. The results of the study indicate that farmers in Margaluyu Village developed several adaptive strategies, such as diversifying income sources by borrowing capital from dealers, using the Tumpang sari technique to overcome challenges arising from the uncertainty of agricultural commodity prices, and forming social networks between farmers. In addition, support from the government and local institutions also plays an important role in strengthening farmers' resilience to market price fluctuations. This study provides in-depth insight into effective survival mechanisms for farmers in dealing with economic uncertainty in the agricultural sector. These findings are expected to be the basis for policy makers in designing programs that support the sustainability of the agricultural sector.